An Overview Of Food Hygiene And Sanitation In Campus C Canteens Universitas Airlangga Surabaya - Ryan Angga Oktafani s (JURNAL KESEHATAN LINGKUNGAN, 2019)
School canteen is provided to meet the confectionary needs of campus citizens at Universitas Airlangga (UA) in Surabaya. Food contamination occurs upon improperly treatment for food, that this issue still potentially happen around the canteen of UA and put significant impacts for campus citizens. This study aims to identify the conditions of hygiene, food handler sanitation and food processing in campus C Airlangga University's canteen. This reearch is a descriptive study with cross sectional design. Sampling process was using purposive sampling method. Observation and exploration regarding hygiene was assessed by questionaire and the sanitation was observed by criteria instrument. Variables of interest in this study are including of the characteristics of food handlers, food handler hygiene, sanitation treatment facilities, canteen facilities and infrastructure on the food provided by the canteen at the University of Airlangga. The results of the study shows that food handlers were free from infectious diseases, they are not smoker and did not comb their hair near food processing premises, only 1 person (of 5%) were sneezing near the food inadvertently. For building sanitation facilities and food preparation areas in each cafeteria is already adequate and already met the criteria of the Decree of the Minister of Health of the Republic of Indonesia No. 1098 / Menkes / SK / VII / 2003, on the feasibility of hygiene and sanitation in the school cafeteria campus.